Entrepreneurial capabilities inherited from previous employment - Sierdjan Koster (European Regional Science Association (ERSA), 2005)
The start-up process of every firm is unique; backgrounds of the founders differ, the goals of the firm differ, sectors differ. However, in firm demographic research there is a continuing quest for regularities in order to understand the start-up process of firms better. In relation to problems with the new foundings birth rate, an important dimension in the start-up process is the influence of existing firms on the start-up of new ones. Is the new firm an individual effort or is the new firm heavily influenced by another firm? This question can be approached from a organisational and an individual perspective. The organisational view takes the firm as a starting point, whereas the individual perspective focuses on the entrepreneur. Both views allow an analysis of the influence of other firms. Taking the organisational viewpoint, new firms can be classified from totally new entities to diversified parts of large existing firms. The former is a totally new configuration of resources, but the latter heavily builds on existing structures and organisation. The processes are pretty straightforward to recognize as the path history of the firms can be traced back pretty easily. However, little is known about the importance of different groups. How many firms are actual new configurations, and how many built upon existing firms? From the individual viewpoint, the influence of other firms is less easily recognised. Many studies reason along the lines of experience. Firms influence the start-up of new ones by educating their employees and giving them expertise in this way. The entrepreneurs use this to start up their own firm. Experienced founders start better firms than other entrants. Several studies have come up with this logically appealing result. After all, it makes sense that entrepreneurs with a reasonable degree of knowledge about the new firm and its sector will perform better than entrepreneurs with less experience. The experience of founders, however, is usually rather loosely defined and in many cases there is only a dichotomy between sector experience (spin-offs) and entrepreneurship experience (habitual entrepreneurs). At the level of the knowledge itself, very little is known and the mechanisms of knowledge transfer from existing firms to new ones are treated as a black-box. Consequently, the role of existing firms as educational institutes for entrepreneurs is only approximately known. This paper focuses on the question to what extent firms are actually new, or that they can be seen as rearrangements of old firms. Which are the most important resources transferred from firm to firm? Both the organisational approach and the individual are applied. The empirical results are based on a large questionnaire (N=347) of Dutch entrepreneurs and a follow-up in the form of focus interviews with the entrepreneurs. It appears that most entrepreneurs have a solid background in the business they are in. About 80% of all entrepreneurs has built up knowledge during their previous job, that they now use being an entrepreneur. Besides 20% of all entrepreneurs even receive direct help from their previous employers. From an organisational perspective, a large share of all firms has been based on existing firms, either as a continuation of a stopped firm (18%), or a diversified part of a larger company (10%). The paper concludes by proposing a framework, based on the above findings, that facilitates a new approach to birth rate calculation methods.
Keywords: 330